Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/w11020375
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence Mechanism of Meteorological Conditions on the Concentration of Suspended Solids and Chlorophyll-a in Large Estuaries Based on MODIS Imagery

Abstract: In estuary areas, meteorological conditions have become unstable under the continuous effects of climate change, and the ecological backgrounds of such areas have strongly been influenced by anthropic activities. Consequently, the water quality of these areas is obviously affected. In this research, we identified periods of fluctuation of the general meteorological conditions in the Yangtze River Estuary using a wavelet analysis. Additionally, we performed a spatiotemporal evaluation of the water quality in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The bands selected to build the Chl-a inverse model are consistent with prior studies [7,66]. Yangtze Mouth and Hangzhou Bay's Chla concentration were analyzed using MODIS satellite's different bands; among them, near-infrared band and red band both achieved good simulation results [28]. Furthermore, the band ratio of blue and red bands was adopted to establish the model of inverse Chl-a concentration of Poyang Lake [13].…”
Section: Applicability Of the Pms-c Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…The bands selected to build the Chl-a inverse model are consistent with prior studies [7,66]. Yangtze Mouth and Hangzhou Bay's Chla concentration were analyzed using MODIS satellite's different bands; among them, near-infrared band and red band both achieved good simulation results [28]. Furthermore, the band ratio of blue and red bands was adopted to establish the model of inverse Chl-a concentration of Poyang Lake [13].…”
Section: Applicability Of the Pms-c Modelmentioning
confidence: 90%
“…The GF-4 geosynchronous optical satellite is currently the world's highest-resolution earth observation satellite in geostationary orbit [28,29]. Its continuous monitoring can make up for the shortcomings of traditional reconnaissance satellites such as low time resolution and small coverage area [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that phytoplankton activity is affected by sea surface temperature [4,11], however, low correlation was observed between chl-a and sea surface temperature (-0.15-0.30) (Table 1). Wind speed is hypothesized to affect TSM because high wind speed results in an increase in flow velocity, which reduces the residence time of coarser grained particles [12]. However, there was low correlation between wind speed and TSM (Table 1).…”
Section: Drivers Of Spatiotemporal Changes Of Chl-a and Tsmmentioning
confidence: 99%
“…Precipitation affects runoff and TSM. TSM can promote chl-a because nutrients can occur as larger suspended solids or are adsorbed on the surface of the particulate matter [12]. The Pampanga River Basin is the largest basin in the Manila Bay Watershed and it discharges into OWT-1 (Figure 1).…”
Section: Drivers Of Spatiotemporal Changes Of Chl-a and Tsmmentioning
confidence: 99%
“…TSS may include a large fraction of mineral seston derived directly from terrigenous sources or indirectly by resuspension of already deposited materials. It is an optically active parameter often referred to as suspended sediment concentration (SSC) and plays a critical role in the management of water resources as they are linked with the fluxes of water contaminants, namely micro-pollutants and heavy metals [7,46,49,63,64], and is a key variable used to describe and control sedimentation dynamics in water bodies [65]. Mineral extraction and energy resources are contributing factors to the increase in TSS in water bodies.…”
Section: Overview Of Tssmentioning
confidence: 99%